Recent Advances on Hydrogels Based on Chitosan and Alginate for the Adsorption of Dyes and Metal Ions from Water - Sanchez-Poblete, J; Alsamman-, M (Elsevier B.V., 2021)
In contemporary times, water resources have become increasingly scarce and suffer from anthropogenic pollution sources with an organic and inorganic origin that are products of industrial, agricultural, and everyday waste. Contamination with heavy metals and dyes in wastewater is considered a risk for water sources that can leak into underground and surface sources, leading to increased biological and chemical contamination. The pollutant removal process is performed by adsorption treatment methods, which is the most common method, and it is considered an effective method with a high and economical removal rate. In this review, we discuss the use of biobased hydrogel adsorbents in the removal of organic dyes and metal ions from water. The literature indicates that hydrogels exhibit rapid absorption kinetics and a dye removal absorption capacity that can reach more than 100 mg/g and sometimes more than 2000 mg/g, with a metal adsorption capacity ranging from 38 mg/g to more than 440 mg/g. These results are discussed and compared by taking into account hydrogel materials that contain biopolymers such as alginate, chitosan or both. In general, absorption depends mainly on biobased materials, which have a natural origin and can be utilized to synthesize hydrogels to remove pollutants, dyes and heavy metals. Chitosan and alginate are prominent materials for this use and they can be incorporated with other components to obtain hydrogels or nanocomposite materials with different efficacies to remove dyes and metal ions. © 2021 The Author(s)